The CXCR1/CXCR2 Inhibitor Reparixin Alters the Development of Myelofibrosis in the Gata1low Mice - Verachi, Paola; Gobbo, Francesca; Martelli, Fabrizio; Martinelli, Andrea; Sarli, Giuseppe; Dunbar, Andrew; Levine, Ross L.; Hoffman, Ronald; Massucci, Maria Teresa; Brandolini, Laura; Giorgio, Cristina; Allegretti, Marcello; et al. (Frontiers in Oncology, 2022)
A major role for human (h)CXCL8 (interleukin-8) in the pathobiology of myelofibrosis (MF) has been suggested by observations indicating that MF megakaryocytes express increased levels of hCXCL8 and that plasma levels of this cytokine in MF patients are predictive of poor patient outcomes. Here, we demonstrate that, in addition to high levels of TGF-β, the megakaryocytes from the bone marrow of the Gata1low mouse model of myelofibrosis express high levels of murine (m)CXCL1, the murine equivalent of hCXCL8, and its receptors CXCR1 and CXCR2. Treatment with the CXCR1/R2 inhibitor, Reparixin in aged-matched Gata1low mice demonstrated reductions in bone marrow and splenic fibrosis. Of note, the levels of fibrosis detected using two independent methods (Gomori and reticulin staining) were inversely correlated with plasma levels of Reparixin. Immunostaining of marrow sections indicated that the bone marrow from the Reparixin-treated group expressed lower levels of TGF-β1 than those expressed by the bone marrow from vehicle-treated mice while the levels of mCXCL1, and expression of CXCR1 and CXCR2, were similar to that of vehicle-treated mice. Moreover, immunofluorescence analyses performed on bone marrow sections from Gata1low mice indicated that treatment with Reparixin induced expression of GATA1 while reducing expression of collagen III in megakaryocytes. These data suggest that in Gata1low mice, Reparixin reduces fibrosis by reducing TGF-β1 and collagen III expression while increasing GATA1 in megakaryocytes. Our results provide a preclinical rationale for further evaluation of this drug alone and in combination with current JAK inhibitor therapy for the treatment of patients with myelofibrosis.